2011
DOI: 10.1901/jaba.2011.44-451
|View full text |Cite
|
Sign up to set email alerts
|

Using Differential Reinforcement of Low Rates to Reduce Children's Requests for Teacher Attention

Abstract: We evaluated the effectiveness of full-session differential reinforcement of low rates of behavior (DRL) on 3 primary school children's rates of requesting attention from their teacher. Using baseline rates of responding and teacher recommendations, we set a DRL schedule that was substantially lower than baseline yet still allowed the children access to teacher assistance. The DRL schedule was effective in reducing children's requests for assistance and approval, and the teacher found the intervention highly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Therefore, even though the participants could tact the contingencies with surprising accuracy, they chose not to respond at all. Of further interest was the fact that many of the studies that have implemented the full‐session DRL schedule used arbitrary reinforcers intended to compete with multiple unknown sources of qualitatively dissimilar reinforcement (e.g., Austin & Bevan, ; Deitz & Repp, ). The current study used only one source of reinforcement and one value of tolerance for each participant, but future research could extend the generality of these findings to multiple sources of reinforcement and multiple values of tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, even though the participants could tact the contingencies with surprising accuracy, they chose not to respond at all. Of further interest was the fact that many of the studies that have implemented the full‐session DRL schedule used arbitrary reinforcers intended to compete with multiple unknown sources of qualitatively dissimilar reinforcement (e.g., Austin & Bevan, ; Deitz & Repp, ). The current study used only one source of reinforcement and one value of tolerance for each participant, but future research could extend the generality of these findings to multiple sources of reinforcement and multiple values of tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Austin and Bevan () used an amalgamation of procedures from both the spaced‐responding and full‐session DRL schedules to decrease requests for help by three typically developing elementary school students. The authors reported considerable decreases in requests during the treatment component.…”
mentioning
confidence: 99%
“…However, a potential limitation of full‐session DRLs is that behavior may be eliminated because a reinforcer can be earned even if a response is not made. Austin and Bevan () reported response elimination for all participants in over half of DRL sessions, but this response elimination may not always be desirable. Requesting assistance in an academic context is adaptive when it occurs at a reasonable rate.…”
mentioning
confidence: 99%
“…GBG = Good Behavior Game. Austin and Bevan (2011) TD children (3) Request for attention DR of low-rate behavior Butler and Luiselli (2007) ASD (1) Disruptive behavior Noncontingent reinforcement and demand fading Harper, Iwata, and Camp (2013) ID (3) Aggression and appropriate interactions DR of appropriate interactions and EXT Jones, Drew, and Weber (2000) ADHD (1) Disruptive behavior Noncontingent peer attention Knox, Rue, Wildenger, Lamb, and Luiselli (2012) ASD (1 Note. DD = developmental disabilities; AGG = aggressive behavior; DR = differential reinforcement; TD = typically developing; ASD = autism spectrum disorder; ID = intellectual disability; EXT = extinction; ADHD = attention-deficit/hyperactivity disorder.…”
Section: Nomentioning
confidence: 99%